ANATOMICAL EFFECTS OF WOOLLY APPLE APHID (ERIOSOMA LANIGERUM HAUS) IN THE APPLE TREE BRANCH - Qaxramanovich, Sayimov Nodir; Raiyimqulovich, Anorbaev Azimjon; Madrimbaevna, Duschanova Guljan (International Journal of Psychosocial Rehabilitation, 2020)
For the first time in Uzbekistan, the anatomical structure of the apple tree trunk (five-star Apple variety) infected with apple blood aphids (Egiosoma lanigerum). And was studied anatomical features, and diagnostic signs characteristic of this variety were identified. When analyzing apples from the point of view of the anatomical structure of the stem of the five-star Apple variety, damaged and undamaged by blood aphids, it was found that biological substances are located in the secondary SAC of the stem parenchyma. When anatomical analysis of the Apple tree trunk damaged by Apple blood aphid, it was found that cells in the secondary parenchyma of the cerebral cortex died and as a result of damage in these tissues, new cells appeared (proliferation) and became tumors.such tumors were recognized as stem cancer and proved on the basis of the identified anatomical features used in the treatment and prevention of tumors of the parietal parenchyma of the Apple tree.